Prevention of Hypertension through Screening and Education for At-Risk Populations in Prancak Glondong - Jihan Fola (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
The prevalence of hypertension based on doctors’ diagnosis in D.I Yogyakarta Province ranks second highest at the national level as reported in the 2018 Basic Health Research. Hypertension prevention is an important pillar of public health, especially in at-risk populations. Hypertension continues to be a public health threat, especially during the COVID-19 pandemic, where patients with comorbid hypertension have a six times higher risk of dying if infected with COVID-19. During the COVID-19 pandemic, non-communicable diseases, including hypertension, are slightly neglected due to the focus on the COVID-19 pandemic. The offered solution is to conduct offline and online screening and education activities related to hypertension. This program aims to mobilize community empowerment to prevent a non-communicable disease, hypertension. Offline and online screening and education activities related to hypertension were carried out on 75 people in 3 RTs (RTs 3, 4, and 5), Prancak Glondong Hamlet, with on-the-job training for cadres. Based on the results of the program, 23% of the screening results showed normal blood pressure. In comparison, the other 48% were found with the ACC/AHA classified as type II hypertension during the examination, with the majority of the age range of 45-65 years (59%). Community development was carried out through job training with three cadres. This program can help reactivate the community empowerment. Health promotion carried out during this community service can increase awareness of non-communicable diseases, especially hypertension.